BENTUK PENYAJIAN MUSIK AGUANG JANA DALAM ACARA PACU JAWI DI KABUPATEN TANAH DATAR - Hidayat Alkara; Syeilendra Syeilendra; Marzam Marzam (SENDRATASIK UNP, 2012)
The purpose of this study Aguang Jana art is to discover and describe the musical art form of presentation Aguang Jana ox racing event in the River District Jorong Guguak Baruah Tarab Tanah Datar. Shaped research used qualitative descriptive method, the object of research is: Music Performance Aguang Jana In no event Pacu Jawi in Jorong Guguak Baruah Tarab River District Tanah Datar, data collection is done by event observation, interviews, and photo shoot perekamam. Data processing is performed a qualitative analysis.  Aguang Jana is a kind of percussion instruments, arts Aguang Jana is a unique art and highly respected community supporters. Plus Aguang Jana has become an essential part in the event at Nagari. This study aims to identify and explain the Music Performance Aguang Jana In no event Pacu Jawi in Jorong Guguak Baruah which includes players / actors, used musical instruments, songs presented in Aguang Jana, time and venue, costume, art Aguang Jana in procession Jawi runway parade and community supporters. Keywords: Traditional music, forms of presentation, pacu jawi event.